Exploring the molecular interactions between neoculin and the human sweet taste receptors through computational approaches - Yousif, Ragheed Hussam; Habibah A. Wahab,; Shameli, Kamyar; Nurul Bahiyah Ahmad Khairudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Neoculin is a sweet taste protein capable of modifying sour taste into sweet taste. Neoculin, along with other sweeteners, are received by the human sweet taste receptors T1R2 and T1R3. To date, there has been few studies regarding how neoculin interacts with the human sweet taste receptors in molecular level. In this study, computational approaches were applied to elucidate how neoculin interact with T1R2 and T1R3 at molecular level. In order to achieve this research, homology modeling for T1R2 and T1R3 was performed to predict their structure. A protein-protein docking study was conducted between neoculin and T1R2 and T1R3, which displayed a strong relationship with the previous experimental findings regarding the important residues of neoculin, and how they interact with the ATD domain of T1R3. These residues are His11, Asp91, Tyr21, Asn44, Arg48, Tyr 65, Val72, and Phe94. The best docked complexes were then subjected to molecular dynamics simulation for further analysis. The molecular dynamics simulation results showed the contributions of the important residues of neoculin in forming hydrogen bonds with the residues of the receptors. The binding energy between neoculin and each of T1R2 and T1R3 were also calculated. These results concluded that neoculin sweet taste and taste modifying abilities are only active when it binds to the amino terminal domain of T1R3.